The Ashgate research companion to modern theory, modern power, world politics critical investigations - Nelson, Scott G.; Soguk, Nevzat (Ashgate research companion, 2016)
This collection of essays deploys political theory as a tool of political interrogation, asking the important question of what rules of truth and truths of rule now govern the times in which we live.